Comparative Analysis of School Revenue and Expenditure Budget Plan Before and During the Covid-19 Pandemic - Noor Amelia; Bella Puspita Rininda (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
A comparative analysis of the RAPBS before and during Covid 19 is an analysis that is important for agencies and the public to know. This study aims to determine a significant decrease or increase in the RAPBS at UPTD SDN 1 Panggung. The data used in this study are secondary data and primary data, namely data obtained directly without intermediaries and data obtained indirectly. The method used in this study was at the time of data collection and at the time the data was collected. This research is in the form of RAPBS UPTD SDN 1 Stage for the 2019 and 2020 fiscal years. The results of this analysis indicate that there are three development components that have experienced increases or decreases, namely the development process standard which has decreased by 16,407,000 IDR or 25%, the development of facilities and school infrastructure decreased by 3,938,000 IDR or 3%, financing development standards experienced an increase of 19,793,865 IDR or 15%. The funds used annually are based on the number of students each year.